The Potential of Ecotourism Development in Water Reservation Area of Mahseer (Tor spp.) in Bungo Regency of Jambi, Indonesia - Aditya, Muhammad Atma; Yulianda, Fredinan; Sulistiono, Sulistiono (Journal of Indonesian Tourism and Development Studies, 2021)
River waters in Bungo Regency are the habitat of mahseer (Tor spp.), which has a potential for ecotourism development. This study aimed to examine the potential of mahseer resources as the main commodity in river ecotourism development. The study was conducted at the Lubuk Alay water reservation area in October 2019. Observations were made for water quality (temperature, depth, transparency, TSS, pH, DO, nitrate, and total phosphate) and general tourism conditions in the region. The analysis was carried out on the river tourism suitability index (TSI), carrying capacity, and management strategies. Based on the observations, the water quality was generally in good condition and suitable for ecotourism requirements. Types of suitable activities for river ecotourism consisted of relaxing sitting-in (TSI 2.08 - 2.45, suitable) with a carrying capacity of 149 persons/day and playing water (TSI 2.35 - 2.45, suitable) with a carrying capacity of 2194 person/day. The management strategies for developing river ecotourism covered the classification of zones in the Lubuk Beringin, ecotourism development in accordance with the existing potential, coordination between the government and public for ecotourism development, and development of ecotourism through improving facilities and infrastructure. Keywords: Carrying capacity, conservation, river ecotourism.